The Association Between Cortisol And Stress Levels In Hypertension Patients - Kai, Meggy Wulandari; Mariana, Evi Risa; Utami, Naning Kisworo; Prayogi, Bisepta (JURNAL CITRA KEPERAWATAN, 2024)
Hypertension is one of the leading causes of morbidity around the world. Between 1990 and 2019, the number of people with hypertension doubled, rising from 650 million to 1.3 billion. Hypertension is defined as high blood pressure with a systolic pressure higher than 140 mmHg and a diastolic pressure higher than 90 mmHg on both measurements taken at a five-minute interval during a period of sufficient rest or calm. Stress is the leading cause of hypertension because it increases cortisol output by the adrenal glands, which leads to hypertension. This study is a literature review which includes completing a journal review applying comparative research methods. The results indicate that there is a link. Cortisol levels and stress levels are linked in hypertensive patients because when stressed, the body releases more stress hormones (adrenaline and cortisol), which activates the Renin Angiotensin Aldosterone System (RAAS), causing blood pressure increase..